ANXIETY ON STUDENTS’ LISTENING COMPREHENSION IN UNIVERSITY STUDENTS IN MALANG - Prastiyowati, Santi (University of Muhammadiyah Malang, 2019)
This study aims at knowing the level of anxiety and factors related to listening anxiety encountered by the students of EFL learners in Malang. This study employs mixed research method, involving forty-eight participants. To gather the data, questionnaires and interview on students’ anxiety are used as the instrument. The results of the study revealed that the students were mostly in moderate-level of anxiety. The anxiety frequently came from students’ background knowledge, such as getting worry to miss important ideas, getting nervous if not understanding every word, getting anxious because of unfamiliar words and topic, and guessing the missing information. Additionally, students’ low confidence in listening process and task, difficulty to concentrate, text speed, and confusion when listening to important information were related to listeners’ characteristic theme. Both contributed to students’ anxiety in their listening performance.Another finding addressed factors which cause students’ anxiety. It can be summarized into four categories, such as teachers’ factor, students’ factors, listening material and process, and another factors. Teachers’ factor related to teachers’’ characteristic and condition. Students’ factors closely related to students’ performance in listening activity. Listening material included listening difficulty and material. Other factors included environmental factors and other situation which was not mentioned in above three factors.